The PROSPECTS FOR MEDICINAL PLANTS CULTIVATION WITH THE WANAFARMA SYSTEM IN MADIUN REGENCY - Marti Winarni; Anang Susanto (International Journal of Multidisciplinary Reseach, 2025)
Medicinal plants are types of plants used to cure diseases suffered by humans directly or indirectly.. The Indonesian people have a close relationship with the forest in their daily lives and possess a high level of traditional knowledge in the use of medicinal plants. The study's purpose supports efforts to develop medicinal types as valuable plant species for herbal medicines, based on the results of field observations and related literature studies. Data and information were collected through direct observations at the location where the medicinal ingredients grow naturally and by reviewing relevant literature studies. Analysis of the potential of medicinal types shows a relatively high potential for medicinal plants with rhizome weights reaching 1 kg The highest habitus type is trees at 45.7%. The lowest habitus type is bushes with 9.5%. Habitat types other than trees are rarely found in the forest because the dense tree canopy blocks sunlight from entering the forest floor. In addition, almost all parts of the tree are utilized